Comparative Study of Greener Alkene Epoxidation Using a Polymer-Supported Mo(VI) Complex: Performance Evaluation and Optimisation via Response Surface Methodology - Md Masud Rana Bhuiyan; Basudeb Saha (Reactions)
A heterogeneous polybenzimidazole-supported Mo(VI) catalyst and tert-butyl hydroperoxide (TBHP) as an oxidising reagent have been utilised to establish a more environmentally friendly and greener alkene epoxidation process. A polybenzimidazole-supported Mo(VI) complex (PBI.Mo) has been prepared, characterised and evaluated successfully. The stability and catalytic activity of the produced catalyst have been evaluated for the epoxidation of 1,7-octadiene and 1,5-hexadiene in a jacketed stirred batch reactor to assess its performance towards these alkenes. The suitability and efficiency of the catalyst have been compared by studying the effect of reaction temperature, feed mole ratio of alkene to TBHP, catalyst loading, and reaction time on the yield of 1,2-epoxy-5-hexene and 1,2-epoxy-7-octene. Response surface methodology (RSM) using Box–Behnken Design (BBD) has been employed to design experimental runs and study the catalytic performance of the PBI.Mo catalyst for all batch experimental results. A quadratic regression model has been developed representing an empirical relationship between reaction variables and response, which is the yield of epoxides. The numerical optimisation technique concluded that the maximum yield that can be reached is 66.22% for 1,7-octadiene and 64.2% for 1,5-hexadiene. The reactivity of alkenes was observed to follow the sequence 1,5-hexadiene > 1,7-octadiene. The findings of this study confirm that the optimal reaction conditions vary between the two reactions, indicating differences in catalytic performance for each alkene.